Molecular Characterization of Pathogenic Isolated from Drinking and Recreational water in East Azerbaijan, Northwest Iran - Hamed Behniafar; Maryam Niyyati; Zohreh Lasjerdi (SAGE Publishing, 2015)
Acanthamoeba -related infections, such as amoebic keratitis and granulomatous amoebic encephalitis, can develop in high-risk population through contaminated water sources. Thus, surveying water resources, particularly those available for human use, is of the utmost importance. In the present study, 67 water samples were collected from water resources in East Azerbaijan, a province in northwestern Iran. Samples were cultured on enriched non-nutrient agar plates, and sequencing-based approaches were used for genotyping. The pathogenic potential of the isolates was determined using thermo- and osmo-tolerance tests. Acanthamoeba were detected in 17 (25.4%) of the 67 collected samples. Sequencing analysis revealed that the isolates belonged to the T3 (23.52%), mixed T3/T4 (5.88%), T4 (58.82%), T5 (5.88%), and T13 (5.88%) genotypes. Through thermo- and osmo-tolerance tests, 88.23% of isolates were resistant to 37 °C, 40 °C temperature, and 0.5 M and 1 M osmolarity; thus, these isolates had the potential for pathogenicity. These findings point toa serious public health concern in the studied region. This study is the first to report Acanthamoeba isolated from drinking and recreational water sources in East Azerbaijan and Acanthamoeba T13 isolated from tap water in Iran.